A "belle epoque"? : women in French society and culture, 1890-1914 - Holmes, Diana, 1949-; Tarr, Carrie (Polygons, 2007)
The Third Republic, known as the 'belle époque', was a period of lively, articulate and surprisingly radical feminist activity in France, borne out of the contradiction between the Republican ideals of liberty, equality and fraternity and the reality of intense and systematic gender discrimination. Yet, it also was a period of intense and varied artistic production, with women disproving the critical nearconsensus that art was a masculine activity by writing, painting, performing, sculpting, and even displaying an interest in the new ""seventh art"" of cinema. This book explores all these f.